Erosion Characteristics and the Corresponding Self-Resonating Oscillations of Cavitating Jet on Oblique Surfaces - Boshen Liu; Fei Ma (Energies, 2020)
The erosion and the corresponding self-resonating oscillations of the cavitating jet were experimentally investigated on the oblique surfaces. To evaluate the intensities of erosion and self-resonating oscillations of the jet, mass loss, surface morphology of the eroded specimens, upstream fluctuating pressure and unsteady cavitation noise were obtained at a series of stand-off distance ratios <semantics> l d / d t </semantics> in the cases where the oblique angles are <semantics> α </semantics> = 0°, 5°, 15° and 30°. In the low <semantics> l d / d t </semantics> range, with the increase of <semantics> α </semantics> , the erosion gradually transforms from two isolated circular erosion rings at <semantics> α </semantics> = 0° into irregular oval shaped rings at <semantics> α </semantics> = 5° and separated horseshoe shaped rings at <semantics> α </semantics> = 15°. The self-resonating oscillations and cavitation were weak in this range because the dominating frequency <semantics> f 0 </semantics> is away from the design frequency of the organ-pipe nozzle, resulting in the depressed aggressive ability in the low <semantics> l d / d t </semantics> range. With increasing <semantics> l d / d t </semantics> , the cavitation is enhanced before the self-resonating oscillations achieving more energy. The spectral decomposition reveals the existence of an intermediate state at the optimum standoff distance, where the energy of self-resonating oscillations and the cavitation reach a balance to realize the severest erosion damage.